ANALISIS KETERGANTUNGAN DAN KEMANDIRIAN KEUANGAN DAERAH DI KABUPATEN SIGI - Sjarifuddin, Nursyamin (Katalogis, 2015)
This study aims to determine the ratio of rgional finance dependency and independency in Sigi district. This study is categorized as a descriptive quantitative research. This study was conducted to obtain the data and information about the regional financial management in Sigi district. This study was conducted in 2014 with the observation period between 2009 and 2013. The data collection was conducted by applying observation, interviews, literature and documentation. Then, it was analyzed by several methods, include: 1) the regional finance dependency ratio is calculated by comparing the amount of regional revenue with total revenues budget without subsidies, and 2) the regional finance independency ratio is calculated by comparing the amount of regional revenue with devided by the budget balance of the Central Government as well as the Province. The result of this study concluded that: 1) The average level of Sigi Region financial dependence on the sentral government during the period of fiscal years from 2009 to 2013 was amounted to 27,05%. When classified according to the criteria of assesment of the level of financial dependence of the central government area is the province with the level of Region Financial Dependence Medium, and 2) The average level of Sigi Regional financial independence area during the period of 2009 to 2013 fiscal years was 1,58%. Therefore, it was categorized as low level of regional financial independency based on the criteria of independence. It is also note that therefore, this district has a high dependency on the central government grants through the balance of funds in implementing regional autonomy and fiscal decentralization during the period of survey.